Reviews. Issue 2 (3rd April 2021) - DeMars, Michelle; Durian, Norma; Parang, Elizabeth
Abstract: Michelle DeMars reviews The Engaged Library: High-Impact Educational Practices in Academic Libraries ; Norma Durian reviews A Trauma-Informed Approach to Library Services ; Elizabeth Parang reviews Supporting Today's Students in the Library: Strategies for Retaining and Graduating International, Transfer, First-Generation, and Re-Entry Students.